PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Nila Rista Anindita; Osmad Muthaher (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to examine the effect of corporate governance, measured by institutional ownership, managerial ownership, independent commissioners, audit committee, and audit quality, on tax avoidance. This research employs a quantitative approach using secondary data obtained from annual reports. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sampling technique used is purposive sampling, resulting in a total sample of 63 companies. The data analysis technique applied in this study is multiple linear regression analysis, processed using SPSS software version 26. The results of this study indicate that corporate governance, as measured by institutional ownership, managerial ownership, independent commissioners, and audit committee, has a negative and significant effect on tax avoidance, while corporate governance measured by audit quality has no significant effect on tax avoidance.